Role of gastric acid inhibition, prostaglandins and endogenous‐free thiol groups on the gastroprotective effect of a proteolytic fraction from Vasconcellea cundinamarcensis latex. (11th September 2014) - Araujo e Silva, Ana Candida; de Oliveira Lemos, Fernanda; Gomes, Marco Túlio Ribeiro; Salas, Carlos Edmundo; Lopes, Miriam Teresa Paz
Abstract Objectives The aim of this study was to extend our knowledge about the mechanism involved in the gastroprotective effect of P1G10, a proteolytic fraction rich in cysteine proteinases from Vasconcellea cundinamarcensis (syn. Carica candamarcensis) latex, which demonstrated gastric healing and protection activities in rats. Methods Wistar rats were submitted to gastric lesions by indomethacin and treated with P1G10 (10 mg/kg). Free thiol groups and prostaglandin E2 content were measured in gastric mucosal and gastrin levels in blood samples. To evaluate the participation of nitric oxide (NO) or proteolytic activity of P1G10 on its gastroprotective effect, animals were treated with an inhibitor of NO production (L‐NAME) or the fraction inhibited by iodoacetamide, respectively. Gastric secretion study (acidity and pepsin activity) was also performed. Key findings P1G10 (10 mg/kg) inhibited the occurrence of gastric lesions by indomethacin, restored the free thiol groups content on gastric mucosa and increased moderately prostaglandin E2 levels (34%). Furthermore, the treatment decreased the gastrin levels (95%), suggesting a possible modulation of secretory activity. This effect was accordant with attenuation of gastric acidity (42%) and pepsin activity (69%) seen in animals subjected to pyloric ligation. The inhibition of NO production or the proteolytic activity of P1G10 does not affect the gastroprotective effect. Conclusions These results can explain the gastroprotective activity of P1G10 and serve a basis for further studies of this active principle.